Pengaruh Pengungkapan Sustainability Report Terhadap Harga Saham Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2020-2022 - Thika Tri Aprilia; Susi Sarumpaet (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The impact of climate change increases public awareness and encourages various parties to realize the importance of sustainability in business and building activities. Companies with a sustainable economy are considered better in the eyes of the public and investors. The sustainability report contains information about the company's social, economic, and environmental performance. Information transparency allows investors to better assess investments that will affect stock prices. Ohlson's (1995) model is used in this study, which is based on Bowerman & Sharma's (2016) research. The three disclosures in the sustainability report together influence the company's stock price, however, if analyzed from every aspect of the disclosure, only social performance has a significant negative influence on the stock price. Thus, the first and second hypotheses in this study were accepted, and the third hypothesis was rejected. The disclosure of economic and environmental performance and sustainability reports affects the share prices of manufacturing companies listed on the IDX for the 2020-2022 period. The company is expected to improve the information disclosed and its quality in the sustainability report. This is so that investors and potential investors can make a more in-depth assessment of the performance and sustainability of a company. Investors should consider more information outside of finance to assess the sustainability of the company in the long term so that the decisions taken will be wiser.